Online Training and Reporting: Natural Resource Governance Institute - Sazen, Noorie (International Journal of Advanced Corporate Learning (iJAC), 2019)
Winner of the IELA E-Learning Award Business Division 2019, Petronia is an innovative game-based learning experience designed by Saffron Interactive for the Natural Resource Governance Institute.